A linear tightly coupled dipole array with wide‐angle scanning. Issue 9 (11th June 2022) - Jia, Yongtao; Hu, Jinhan; Liu, Ying; Liu, Zhong‐Xun
Abstract: A low‐profile linear tightly couple dipole array (TCDA) with wide impedance bandwidth and wide‐angle scanning is proposed in this letter. To implement the design concept of TCDA in a linear array, vertical metal walls are loaded on two sides of the array, which aims to provide the electromagnetic boundaries that are destroyed in the initial linear TCDA. Slots are notched on the ground plane, so as to increase the capacitance at low frequency and then to improve the impedance bandwidth. Simulated results show that the proposed linear array can achieve a 3.1:1 bandwidth from 3.8 to 11.6 GHz with VSWR <3:0, and the maximum scanning angle is up to ±60°. The total profile of the proposed arrays is only 0.13 free‐space wavelength at the lowest operating frequency. A 1 × 18 linear array prototype is finally fabricated and measured. The measured results agree well with the simulated ones.